Introduction to the music industry : an entrepreneurial approach - Fitterman Radbill, Catherine (Routledge, 2013)
"Introduction to the Music Industry: An Entrepreneurial Approach is an introductory textbook that offers a fresh look at one of the fastest-changing businesses int eh world today. Emphasizing the importance of entrepreneurial thinking for the music industry, this textbook engages college-level students in learning the fundamentals of the music business while discovering ways to shape the industry's future. Every chapter explores the inner workings of the music industry, using creative problem-solving exercises, and inspiring stories of actual music entrepreneurs. The textbook's companion website provides multimedia content, study guides, and an instructor's manual with lesson plans and suggestions for assessing students' work."--Provided by publisher.